2021
DOI: 10.3390/risks9020033
|View full text |Cite
|
Sign up to set email alerts
|

Forward-Looking Volatility Estimation for Risk-Managed Investment Strategies during the COVID-19 Crisis

Abstract: Under the impact of both increasing credit pressure and low economic returns characterizing developed countries, investment levels have decreased over recent years. Moreover, the recent turbulence caused by the COVID-19 crisis has accelerated the latter process. Within this scenario, we consider the so-called Volatility Target (VolTarget) strategy. In particular, we focus our attention on estimating volatility levels of a risky asset to perform a VolTarget simulation over two different time horizons. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Mefteh and Romdhane (2022, p. 308) stress that economic growth was further impacted by unemployment because of the negative relationship between unemployment and economic growth, as the decline in investment contributed to a rise in unemployment. A study by Di Persio, Garbelli and Wallbaum (2021) confirms that the pandemic led to substantial volatility within risky assets and investments. In times of uncertainty, such as the peak period of the pandemic, Al-Thaqeb and Algharabali (2019, p. 2) stress that the impact thereof on households, businesses and governments' investment and spending is significant.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Mefteh and Romdhane (2022, p. 308) stress that economic growth was further impacted by unemployment because of the negative relationship between unemployment and economic growth, as the decline in investment contributed to a rise in unemployment. A study by Di Persio, Garbelli and Wallbaum (2021) confirms that the pandemic led to substantial volatility within risky assets and investments. In times of uncertainty, such as the peak period of the pandemic, Al-Thaqeb and Algharabali (2019, p. 2) stress that the impact thereof on households, businesses and governments' investment and spending is significant.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Optimality restrictions in some cases lead to portfolio segregation. In the same vein, recent studies by [19] have shown that the turbulence produced by Covid-19 has generated significant volatility in terms of investments and risky assets. The research also discusses the issue of sustainability in the context of limited resources and their diverse allocation needs.…”
Section: Introductionmentioning
confidence: 94%
“…Di Persio et al . 2021 and references therein). In the present study, we take a simplified approach and use the annualized historical volatility estimated over the most recent 20 business days.…”
Section: The Dynamic Target Volatility Strategymentioning
confidence: 99%